RNA-Seq Reveals miRNA Role Shifts in Seven Stages of Skeletal Muscles in Goat Fetuses and Kids - Ling, Yinghui; Zheng, Qi; Jing, Jing; Sui, Menghua; Zhu, Lu; Li, Yunsheng; Zhang, Yunhai; Liu, Ya; Fang, Fugui; Zhang, Xiaorong (Frontiers in Genetics, 2020)
MicroRNAs (miRNAs) are indispensable for the regulation of skeletal muscle. We performed RNA sequencing (RNA-seq) to establish a comprehensive miRNA profiling of goat seven stages, including 45 (F45), 65 (F65), 90 (F90), 120 (F120), 135 (F135) days fetuses, newborn (B1) and born 90 (B90) days kids. Totally, 421 known miRNAs and 228 goat novel miRNAs were identified in the data, and the average abundance of 19 miRNAs in seven stages exceeds 10,000 reads per million (RPM). Furthermore, 420 differentially expressed miRNAs (DEmiRNAs) were identified in all comparison group at seven stages, 80 of which were uniquely differentially expressed in the B1 and B90 comparison groups. Pathway analysis indicated that this group was associated with the release of muscle hypertrophy and regulation of myoblast proliferation. Besides, 305 DEmiRNAs were clustered into 3 significantly enriched profiles (profile 11, 16 and 19). Function analysis revealed profile 16 was related to muscle hypertrophy and differentiation. Profile11 was involved in multiple enzyme activities and metabolic processes in muscle cells. And profile19 was involved in material transport and structural stability. Two high expressed miRNAs and three key miRNAs (chi-miR-328-3p, chi-miR-767 and chi-miR-150) of these profiles were verified to be consistent with the data by qRT-PCR. These results provided a catalog of goat muscle-associated miRNAs, allowing to better understand the transformation of miRNA roles during mammalian muscle development.